Multiple Linear Regression Equations to Estimate the Body Weight of Waringin Sheep Based on Morphometric Characteristics in Various Age Groups. - Maibang, W.S; P. Patriani; Alwiyah (Jurnal Peternakan Integratif, 2023)
Waringin sheep is a new breed of sheep resulting from a cross between local sheep, Barbados sheep and St.Croix sheep. This study aims to determine the morphometric characteristics of ewes and rams Waringin sheep at different ages in Stabat District, Langkat Regency. This study used a descriptive method by collecting data in the field, the data collected were 99 ewes Waringin sheep and 66 rams Waringin sheep and observed their morphometric characteristics starting from body weight, body length, skull length, skull width, body height, and chest circumference, chest width, chest depth, front leg length, hind leg length, hip width, hip height, tail length, tail width, crotch length, crotch width, and canon circumference. Data were analyzed using the SPSS application with multiple linear regression methods used to determine the relationship between the morphometric relationship between Waringin sheep and their body weight. The results showed that almost 90% of the morphometrics of Waringin sheep affected the body weight of the sheep using linear regression analysis.